The Implementation of JiRQA Model to Improve Biology Learning Outcomes at Indonesia Junior High School - Bustami, Yakobus; Wahyuni, Florentina Rahayu Esti (Jurnal Pendidikan MIPA, 2023)
Abstract: Biology is a material that requires an understanding of students' learning outcomes. This research aims to determine the effect of the JiRQA learning model on the learning outcomes of class VIII students at Yoseph Khatulistiwa Middle School and Nusantara Indah Sintang Middle School. This research was a quantitative approach with a weak experiment design method. The population was all class VIII students at Yoseph Khatulistiwa Middle School and Nusantara Indah Sintang Middle School, consisting was 29 students, 16 students at Yoseph Khatulistiwa Middle School and 13 students at Nusantara Indah Sintang Middle School. The instrument to measure students' learning outcomes is in the form was 20 multiple choice questions. The data obtained was analyzed using descriptive statistical analysis and inferential analysis in the form of a paired sample t test. The results of descriptive statistical analysis showed an increase in the average pretest and posttest scores was 38.62%. The results of inferential statistical analysis show that the significance value for learning outcomes was 0.000 and is greater than alpha 0.05, so it can be concluded that there is a significant influence of the implementation of the JiRQA learning model on students' learning outcomes in Biology material. Keywords: JIRQA learning model, learning outcomes, biology learning. Abstrak: Biologi merupakan materi yang memerlukan pemahaman terhadap prestasi belajar siswa. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran JiRQA terhadap prestasi belajar siswa kelas VIII di SMP Yoseph Khatulistiwa dan SMP Nusantara Indah Sintang. Penelitian ini merupakan penelitian kuantitatif dengan metode weak eksperimen. Populasi adalah seluruh siswa kelas VIII SMP Yoseph Khatulistiwa dan SMP Nusantara Indah Sintang yang terdiri dari 29 siswa, 16 siswa SMP Yoseph Khatulistiwa dan 13 siswa di SMP Nusantara Indah Sintang. Instrumen untuk mengukur prestasi belajar siswa berupa 20 soal pilihan ganda. Data yang diperoleh dianalisis menggunakan analisis statistik deskriptif dan analisis inferensial berupa Paired sample t test.. Hasil analisis statistik deskriptif menunjukkan adanya peningkatan rata-rata skor pretest dan posttest sebesar 38,62%. Hasil analisis statistik inferensial menunjukkan nilai signifikansi prestasi sebesar 0,000 lebih besar dari alpha 0,05 sehingga dapat disimpulkan bahwa terdapat pengaruh yang signifikan penerapan model pembelajaran JiRQA terhadap prestasi belajar siswa pada materi Biologi.  Kata kunci: model pembelajaran JIRQA, prestasi belajar, pembelajaran biologi. DOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp690-698